Analisis Penilaian Kinerja Keuangan Perusahaan dengan Menggunakan Metode Economic Value Added (EVA) Pada PT. Bank Rakyat Indonesia (Persero) Tbk - Lihawa, Maullanah; Montolalu, Johny; Tampi, Dolina (Sam Ratulangi University, 2018)
The purpose of this research is to know the company's financial performance by using economic value added (EVA) method at PT. Bank Rakyat Indonesia (Persero) Tbk. During the period 2015 - 2017. Economic Value Added Analysis (EVA) is one way to explore financial performance. Economic Value Added (EVA) is an indicator of the implementation of investment. To process the data that have been collected from the results of research, the researchers in this research using the analysis of corporate financial performance using the method of Economic Value Added (EVA) by calculating Net Profit After Tax, calculate Invested Capital, calculate Average Cost Of Capital, calculate Capital Charges and Calculate Economic Value Added (EVA). After processing the results data show that the financial performance of PT. Bank Rakyat Indonesia (Persero) Tbk during the period of 2015 until 2017 EVA value continues to increase EVA value in every year of research. This proves that the company's managers are able to create economic value added for the company by maximizing profits that contribute to the increasing value of NOPAT and minimize the return on risk in infestation that causes the decline in Capital Charges value resulting in EVA> 0 value. The results show that during the period 2015 to 2017 PT. Bank Rakyat Indonesia (Persero) Tbk. get a positive value with the highest EVA in 2017 of Rp. 21,396,554 (in millions of rupiahs) because in that year the company had the highest NOPAT from the previous two years and had Capital Charges which is low enough so that the company can obtain higher value added from 2015 and 2016. Then in 2016 the company has EVA lower of Rp 19,298,437 (in millions of rupiah) with the difference of 9.80% compared to the year 2017 and the creation of the lowest value in 2015 amounting to Rp. 17,231,693 (in millions of rupiah) with a difference of 10.70% compared to the value of EVA in 2016.Key Words : Analisis Economic Value Added (EVA), Financial Performance.